The Political Economy of Industrial Development in Thailand - Shangmao Chen (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2014)
Since the 1990s, governments around the world have emphasized the core concepts of globalization. Many governments initiated a series of political policies regarding liberalization and privatization in response to the inevitable phenomenon. In Southeast Asia, Thailand participated in the development as well by reconstructing its financial system to allow greater foreign capital for investments. Unfortunately, the importance of prudential regulations was underestimated, and the neglect thereafter caused the Asian Financial Crisis which initially occurred in Thailand on the second of June, 1997. The Thai government received 17.2 billion US dollars from the International Monetary Fund (IMF) to stabilize its domestic situation and implemented structural reform to minimize losses from the crisis. Meanwhile, different voices regarding the policies for globalization were expressed. These opinions mainly referred to regionalization/ regionalism and localization/ localism. This study discusses how the Thai state transformed under globalization from three industries: the Telecommunication industry, the Automobile industry, and the Cultural Creative industry. This article observes that Thailand turned to take regionalization and localization into consideration, which in turn demanded the state to increase domestic autonomy and capacity. The findings also suggest that cooperation with other governments in the region to accelerate economic recovery from the crisis was inevitable. However, political instability and close state-business relations continue to make the future of Thailand uncertain.